Terceirização na educação superior: o trabalho docente por meio de cooperativas de mão-de-obra - Adolfo Ignacio Calderón; Francine Martins; Henrique da Silva Lourenço; Raquel de Moraes (EccoS – Revista Científica)
In this article, we propose an understanding of a new phenomenon present in management of private higher education institutions. In this point of view it is an outsourcing labor through a cooperative society. It is a controversial subject in which some institutions of higher education made the outsourcing teachers work responsible for the teaching-learning process.